Copper-catalyzed borylative aminomethylation of C–C double and triple bonds with N, O-acetal. Issue 26 (2nd March 2021) - Qiu, Xianfan; Xu, Liugen; Wang, Shuxia; Dai, Ying; Feng, Yunqiu; Gong, Chang; Tao, Chuanzhou
Abstract : A copper-catalyzed borylaminomethylation of multiple carbon–carbon bonds with N, O -acetal and bis(pinacolato)diboron has been disclosed that offers efficient and expedient access to γ-amino boronates. Abstract : A copper-catalyzed borylaminomethylation of multiple carbon–carbon bonds with N, O -acetal and bis(pinacolato)diboron has been disclosed that offers efficient and expedient access to γ-amino boronates. The products contain a valuable amine and boronate, which are amenable to further elaboration, and have versatile synthetic utilities.